A New Species of Tagalis Stål, 1860 (Hemiptera, Reduviidae, Saicinae) from Argentina - Varela, Pablo Sebastian (2017)
A new species, Tagalis drakkar n. sp., is described from Misiones, Argentina. It is easily separated from the other species of the genus by the particular shape of the median process of the pygophore and other male genitalic structures, and the overall pale coloration. We also describe the male aedeagus of Tagalis femorata Melo (2008) and discuss the affinities of the two species studied in the context of species groups proposed by Castro-Huertas and Forero (2014).